Project-based approach in education - Zapesotskaya, Irina V.; Vetrenko, Ekaterina A.; Umirzakova, Zaure A.; Babaskin, Dmitrii V. (Opción, 2020)
The purpose of our research is to conduct semi-structured interviews with Russian students, as well as with the students studying in one of Kazakhstan's universities in order to find out their attitude to project activities via semi-structured interviews related to project activities with Russian and Kazakhstan students. As a result, the Portuguese study does not focus on the skills that students can develop through participating in project activities and the participants do not provide their description of project activities. It can be concluded that project activities are an integral part of the educational process.